Newman and Strossmayer on the relationship between the Church and the State : (I) - Šokčević, Šimo (Array, 2020)
The relationship between the Catholic Church and the state, and between the Church and the state in general, is a very topical issue, and theoreticians at the present time provide various models that render assistance to the comprehension of that relationship. The complexity and extensiveness of the problem necessitates that it should be dealt with in two parts (articles). Basically, our objective was to represent the deliberations of John Henry Newman (1801‒1890) and Josip Juraj Strossmayer (1815‒1905), which we consider to be exceptionally valuable and relevant even today. Through such an analysis, we intended to examine how the deliberations of these two great thinkers of the nineteenth century may contribute to a better cooperation between the Catholic Church and the state in present‐day Europe. In this, the first article, in which we deal with Newman’s and Strossmayer’s perceptions of the relationship between the Catholic Church and the state, at the very outset we feature the context in which Newman and Strossmayer each take a closer look at that relationship. This context is characterized by liberalism, but with numerous negative connotations that suffocate the originally positive meaning of liberalism. A negative context of liberalism is an aggravating circumstance in the comprehension of the relationship between the Catholic Church and the state, and on the other hand, from the position of a modern liberal state, Newman’s and Strossmayer’s comprehension of history, in whose center is the principle of God’s Providence, is also qualified in this way, which simultaneously renders the Catholic Church consistent and authentic, unlike the modern liberal state, which frequently assumes utopian and ideological characteristics. For this very reason, that difference regularly seems insurmountable.